Implementasi Bank Sampah Pada ST. Kerta Budi Luhur untuk Pengelolaan Sampah Organik dan Anorganik - I Made Arya Budhi Saputra; I Nyoman Rudy Hendrawan; Deviana Deviana (Indonesian Journal Publisher, 2021)
ST. Kertha Budi Luhur is the youth organization of the Kayumas Kelod traditional banjar which was founded around 1995. One of the social activities of the Sekaa Teruna is to focus on environmental and waste issues. Related to the issue of waste ST. Kertha Budi Luhur plans to establish a waste bank. The waste bank is an alternative solution that can be done by the community in terms of waste management or management. Waste banks can increase public participation to care more about the waste they produce daily, besides that, with the existence of waste banks, the community can get economic value feedback. Therefore, in this community service, socialization and training were carried out on how to form a waste bank. This community service activity is broadly divided into initial socialization activities aimed at providing initial information about waste banks and technical training activities aimed at providing a more detailed explanation of the waste bank operations, from sorting waste to working with garbage collectors. Increased awareness of waste management by 85% of ST members Kertha Budi Luhur after the training.